Management of Pneumothorax and Prolonged Air Leak - Slade, Mark (Seminars in Respiratory and Critical Care Medicine, 2014)
Pneumothorax refers to the presence of air within the pleural cavity, which may arise from a spontaneous defect in the visceral pleural surface, or through iatrogenic or other thoracic trauma. The most common cause in the developed world is iatrogenic pneumothorax. Most frequently, it can be managed conservatively or through simple pleural aspiration or drainage. A persistent air leak, >2 days' duration, develops in one-third of patients. When patients are managed with chest drainage alone, the median time for resolution of air leak is longer in patients with a pneumothorax secondary to an underlying lung disease (11 vs. 7 days). Interventional pulmonology is not usually required for the resolution of simple pneumothorax, but offers important minimally invasive techniques for treating persistent air leak and bronchopleural fistula. Following assessment of the site of the air leak within the bronchial tree, techniques are described for the sealing of leak using tissue or fibrin glues, endobronchial devices of various kinds, and combination approaches. Bronchoscopic sealing of air leaks can often avoid the requirement for thoracic surgical intervention. They may prove life-saving in patients who are difficult to wean from mechanical ventilation or extracorporeal membrane oxygenation because of catastrophic air leaks.
Keywords: pneumothorax; bronchopleural fistula; prolonged air leak; endobronchial valve; interventional bronchoscopy